Genotypes of Enterocytozoon bieneusi in livestock in China: high prevalence and zoonotic potential. - Wei Li; Yijing Li; Weizhi Li; Jinping Yang; Mingxin Song; Ruinan Diao; Honglin Jia; Yixin Lu; Jun Zheng; Xichen Zhang; Lihua Xiao (PLoS ONE, 2014)
Despite many recent advances in genotype characterization of Enterocytozoon bieneusi worldwide and the exploration of the extent of cross-species transmission of microsporidiosis between humans and animals, the epidemiology of this neglected disease in China is poorly understood. In this study, a very high prevalence (60.3%; 94/156) of E. bieneusi infections in farmed pigs in Jilin province was detected by PCR of the ribosomal internal transcribed spacer (ITS). DNA sequence analysis of 88 E. bieneusi-positive specimens identified 12 distinct genotypes (11 known: CHN7, CS-1, CS-4, CS-6, EbpA, EbpB, EbpC, EbpD, EBITS3, G, and Henan-I; one novel: CS-9). Frequent appearance of mixed genotype infections was seen in the study animals. Weaned (74.6%; 53/71) or pre-weaned (68.8%; 22/32) pigs have infection rates significantly higher than growing pigs (35.8%; 19/53) (p<0.01). Likewise, E. bieneusi was detected in 2 of 45 sheep fecal specimens (4.4%) in Heilongjiang province, belonging to the known genotype BEB6. Genotypes EbpA, EbpC, EbpD, and Henan-I examined herein have been documented in the cases of human infections and BEB6, EbpA, EbpC, and EbpD in wastewater in central China. Infections of EbpA and EbpC in humans were also reported in other areas of the world. The other known genotypes (CHN7, CS-1, CS-4, CS-6, EBITS3, EbpB, and G) and the new genotype CS-9 were genetically clustered into a group of existing E. bieneusi genotypes with zoonotic potential. Thus, pigs could be a potential source of human E. bieneusi infections in China.